EDUCATING DIGITAL LIBRARIANS: EXPECTATIONS, REALITIES AND FUTURE PERSPECTIVES - Varalakshmi, R. S. R. (Malaysian Journal of Library and Information Science, 2003)
The training for library and information professional is essential for effective functioning of the libraries and information society in general. It is natural for LIS profession to expect the LIS schools to produce graduates suitable for their needs. Similarly, students have high expectations from their academic programmes. They want the programmes to mould them as Knowledge Managers with high capabilities irrespective of their back ground qualifications. Hence the pressure is on LIS schools or/ departments to cope with the demands. This necessitates redefining and reengineering their goals, subject jurisdiction and programmes. However effective implementation of the set goals depends on several issues. The article presents an over view of the associated issues and their variant format of application. Suggestions have been made on how to handle the issues and cope with the future perspectives of LIS education programmes.